Energy: a necessary change in Peru - Gamio Aita, Pedro (2017)
In this article we examine the actual situation of our country regarding the excessive use of pollutant energy (mainly based in hydrocarbons), as well as the problematic of a gradual change to cleaner and renewable energy which will allow us to face the climate change. In addition, the need of public politics to promote the sustainable and healthy development of our country is posed, because governability problems and lack of institutionality may their execution difficult. We also analyze the great potential of renewable energies such as eolic and geothermal among others.